The influence of design character on logo recall / Muhamad Abdul Aziz Ab Ghani - Ab Ghani, Muhamad Abdul Aziz (Institute of Graduate Studies, UiTM, 2015)
Logo is an important part of branding aspect especially in creating an identity for the brand. The definition of a logo actually is virtually limitless and cannot be restrict in today’s globalized and borderless world. The reason is the growth and evolution of logo design has made a logo being valued not only from the definition aspect, but going further as a medium for communication and conveying messages (Armstrong, 2009). Nevertheless, in theory, a logo must at least easy to be remembered and recognize, as mentioned by Klerkx & Meurs (2006) that a logo design must emphasize on the elements that are easily remembered by the audience and thus, the brand represented by the logo is more well-known than competitors. Once a brand is known, the products will have more sales potential. This, according to Haig & Harper (1997) depends on the role and function of a logo design, which is to be easily remembered. From the basic principle of a logo design that is to make it easy to be remembered, several important questions arises through a research process. The most important question is what is the most significant factor that makes a logo easy to be remembered. As the result, this research focused on design characters exist in a logo design which involve shape, line, colour, typography, and image in finding the most significant factor in making a logo easy to be remembered. There are three objectives outlined for this research. The first one is to explore the design characteristic of logos used in Peninsular Malaysia’s SME companies and product. The second objective is to determine which of the design characteristic that are more easily recognize and remember…